Infiltration of F98 glioma cells in Fischer rat brain is temporary stimulated by radiation. (2nd August 2016) - Desmarais, Guillaume; Charest, Gabriel; Therriault, Hélène; Shi, Minghan; Fortin, David; Bujold, Rachel; Mathieu, David; Paquette, Benoit
Abstract: Purpose: Irradiation of brain stimulates the expression of inflammatory mediators, some of which can modify the ability of cancer cells to infiltrate the brain. In the present study, the time window during which this stimulation occurs was determined. Materials and methods: Brain of Fischer rat was irradiated (15 Gy) and expression of pro-inflammatory mediators IL-1β, IL-6 and TNF-α was measured from 4 h to 20 days post-irradiation. Level of the matrix metalloproteinase 2 (MMP-2) and prostaglandin E2 (PGE2) which can favor cancer cell infiltration were also measured. The F98 glioma cells were implanted either during (4 h post-irradiation) or after (10 days post-irradiation) the pro-inflammatory phase. Infiltration distance of F98 cells in brain parenchyma and the median survival time of the animals were determined. Results: Expression of IL-1β, IL-6 and TNF-α was significantly increased in the irradiated brains with a peak at 4 h post-irradiation. Implantation of F98 glioma cells 4 h post-irradiation reduced the median survival time of Fischer rats to 18 days, compared to 25 days when the F98 were implanted in non-irradiated brain. Irradiation of the brain increased the distance of infiltration of F98 cells and was associated with increased levels of MMP-2 and PGE2. Conversely, F98 cells implanted 10 days post-irradiation have infiltrated the brain over a shorter distance and the median survival time of rats was increased to 35 days. Conclusions: Cancer recurrence is frequently observed in GBM patients. A better understanding of the inflammatory response observed in irradiated brain could contribute to develop new therapeutic modalities to further increase the efficiency of radiotherapy.